2018
DOI: 10.3390/molecules23092307
|View full text |Cite
|
Sign up to set email alerts
|

Quality Evaluation of Phellodendri Chinensis Cortex by Fingerprint–Chemical Pattern Recognition

Abstract: Phellodendri Chinensis Cortex (PCC) and Phellodendri Amurensis Cortex (PAC) are increasingly being used as traditional herbal medicines, but they are often mistaken for each other. In this study, the fingerprints of PCC from six different geographical sources were obtained by high-performance liquid chromatography, and multivariate chemometric methods were used for comprehensive analysis. Two unsupervised pattern recognition models (principal component analysis and hierarchical cluster analysis) and a supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 16 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…Principal components (PCs) were selected from the obtained eigenvalues, the first three PCs accounted for 76.9% of the total variance, which were enough to describe the variability. The cross‐validation coefficient was Q 2 (cum) = 0.415, which indicated that the model was reasonable and had good analytical and predictive ability [28]. The 3D score plot is shown in Figure 3A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Principal components (PCs) were selected from the obtained eigenvalues, the first three PCs accounted for 76.9% of the total variance, which were enough to describe the variability. The cross‐validation coefficient was Q 2 (cum) = 0.415, which indicated that the model was reasonable and had good analytical and predictive ability [28]. The 3D score plot is shown in Figure 3A.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, at a confidence level of 95%, the cumulative contribution rates were R 2 X (cum) = 0.731 and R 2 Y (cum) = 0.882, the cross‐validation Q 2 (cum) in the OPLS‐DA model was 0.719. Thus, compared with PCA, it could explain most of the variance of the data and has a greater fitting and predictive ability [28]. The 2D score plot is shown in Figure 3B, from which the separation of CQ and DQ can be clearly observed.…”
Section: Resultsmentioning
confidence: 99%
“…In HCA, a dendrogram was obtained to characterize the classification results of the different sample sets by Ward's linkage as a cluster method. PCA was used to analyze and describe the distribution of the studied sample as it could explain most of data variance with a greater fitting and predictive ability [19]. Besides, PLS-DA can maximize the difference among the groups and screen out key markers that could be responsible for sample variation [21,22].…”
Section: Chemical Pattern Recognition Analysismentioning
confidence: 99%
“…PLS-DA is a supervised CPR method to optimize classification and to screen out key markers responsible for sample variation. Many researchers have reported the quality assessment of TCMs with distinct classification of test samples on the basis of their different components using PLS-DA after comparing SA, HCA, and PCA [19,24,25]. In the PLS-DA model, R 2 X (cum) and R 2 Y (cum) are two parameters that are often calculated by the cross-validation procedure to evaluate the goodness of fit, while Q 2 (cum) is a parameter used to describe the validity of the model.…”
Section: Partial Least Squares Discriminant Analysismentioning
confidence: 99%
See 1 more Smart Citation